Microgeographic genetic variation of the malaria vector Anopheles darlingi Root (Diptera: Culicidae) from Cordobá and Antioquia, Colombia (2010)
ABSTRACT : Anopheles darlingi is an important vector of Plasmodium spp. in several malaria-endemic regions of Colom-bia. This study was conducted to test genetic variation of An. darlingi at a microgeographic scale (approximately 100 km) from localities in Córdoba and Antioquia states, in western Colombia, to better understand the potential contribution of population genetics to local malaria control programs. Microsatellite loci: nuclear white and cytochrome oxidase sub-unit I ( COI ) gene sequences were analyzed. The northern white gene lineage was exclusively distributed in Córdoba and Antioquia and shared COI haplotypes were highly represented in mosquitoes from both states. COI analyses showed these An. darlingi are genetically closer to Central American populations than southern South American populations. Overall microsatellites and COI analysis showed low to moderate genetic differentiation among populations in north-western Colombia. Given the existence of high gene flow between An. darlingi populations of Córdoba and Antioquia, integrated vector control strategies could be developed in this region of Colombia.